Probing 2D magnetism through electronic tunneling transport - Gen Long (Elsevier, 2021)
Atomically thin van der Waals magnetic materials have gained intensive research interests in the past few years. The topic paves a way to understand the stabilization and dissipation mechanisms of long-range magnetic order in the 2D limit, which is crucial for both fundamental condensed matter physics research and technological applications. However, limited by the sample size, conventional experimental techniques such as neutron diffraction spectrum and magnetization measurements are difficult to be applied to these atomically thin materials. At the same time, electronic tunneling transport measurements have been proved to be a powerful technique in the study of 2D magnetism. Here we review the electronic tunneling transports in magnetic 2D crystals, especially the detection of the phase boundaries of 2D magnets, focusing on two-material systems, i.e. chromium halides and manganese phosphorus trisulfides. In addition, the magnetic van der Waals Josephson junctions and the spin valve devices based on the 2D magnetic metals are applied to probe 2D magnetism as well. Finally, we discuss the current challenges and perspectives of potential applications of 2D van der Waals magnetic materials.